Studi eksperimental tentang pengaruh diesel particulate filter terhadap reduksi tingkat kebisingan mesin diesel empat langkah - Warju, W.; Ariyanto, S. R.; Soeryanto, S. (Dinamika Teknik Mesin, 2020)
The purpose of this research is to produce DPF technology made from copper plates and glass wool that can reduce the noise level of four-stroke diesel engine vehicles. This research is an experimental research where the object of research used is Isuzu Panther 1996. The research instruments used include the chassis dynamometer, sound level meter (SLM), and manometer. The data analysis technique used descriptive method and compared with the noise threshold in Minister of Environment Regulation No. 07 of 2009. The results showed that DPF Cu and 100 gr glass wool was able to reduce noise level by an average of 3.1% to 6.5%. At an engine speed of 3750 rpm, DPF Cu 20 mm, DPF Cu 15 mm, and DPF Cu 10 mm and 100 gr glass wool, each produced noise level of 101.5 dBA, 98.4 dBA, and 97.8 dBA.